Psychoeducational study on child sexual abuse: an example of a focus group of experts from the film precious. - Campo-Redondo, María; Pereira Domínguez, Carmen (Opción)
The aim of this article is to present a guided pedagogic proposal, which serves to illustrate through the movies, concepts related to psychodynamics of psychological child trauma due to sexual abuse. For the development and validation of this proposal, a Focus Group of Experts (GFE) was gathered to analyze the film Precious. Guiding questions posed to the group are described, the most significant ideas that emerged from the discussion are presented, and also, an example of pedagogic intervention of the film is presented here. It”™s concluded that the viewing of this film, and discussion of the coordinates that arise from its analysis, may be useful as supplementary material to the academic education of the phenomenology of trauma for domestic violence and child sexual abuse.